Development of Interactive Web Learning Media Based on Problem-Based Learning on the Topic of Work Energy and Simple Machines for Junior High School Students - Komang Regina Triana; Nia Erlina; Putri Sarini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The rapid development of digital technology in education requires innovative learning media to support students’ problem-solving skills in science learning. This study aims to develop an interactive web learning media based on problem-based learning on the topic of work, energy, and simple machines for junior high school students. This research employed a Research and Development (R&D) approach using the ADDIE model, focusing solely on the development stage. The data were collected using validation questionnaires (content, media, and language) and practicality questionnaires for teachers and students. The validation data were analyzed using the Gregory validity coefficient, while the practicality data were analyzed using descriptive statistical analysis. The validity test was conducted by two experts in content, media, and language relevant to their respective fields. The practicality test involved three science teachers and twelve students of SMP Negeri 1 Seririt. The results showed that the KVG for content validity was 0.95, while the media and language validity reached 1.00, both categorized as very high validity. The teacher's practicality score was 100, and the student's practicality score was 44.66, both categorized as very practical. These findings indicate that the developed interactive web-based learning media is valid and practical, and has the potential to support the development of students’ problem-solving skills in learning the concepts of work, energy, and simple machines.